1999
DOI: 10.1146/annurev.physiol.61.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Basis for Electrical Rhythmicity in Gastrointestinal Muscles

Abstract: Regulation of gastrointestinal (GI) motility is intimately coordinated with the modulation of ionic conductance expressed in GI smooth muscle and nonmuscle cells. Interstitial cells of Cajal (ICC) act as pacemaker cells and possess unique ionic conductances that trigger slow wave activity in these cells. The slow wave mechanism is an exclusive feature of ICC: Smooth muscle cells may lack the basic ionic mechanisms necessary to generate or regenerate slow waves. The molecular identification of the components fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 115 publications
2
155
0
Order By: Relevance
“…Molecular identification of ion channels important to smooth muscle function allows analysis of their biophysical, pharmacological, and regulatory properties in heterologous systems (20). In the present study, we have identified the molecular entity responsible for a component of stretch-activated K ϩ channels in gastrointestinal smooth muscle cells.…”
Section: Many Different Kmentioning
confidence: 84%
“…Molecular identification of ion channels important to smooth muscle function allows analysis of their biophysical, pharmacological, and regulatory properties in heterologous systems (20). In the present study, we have identified the molecular entity responsible for a component of stretch-activated K ϩ channels in gastrointestinal smooth muscle cells.…”
Section: Many Different Kmentioning
confidence: 84%
“…Smooth muscle cells lack the ionic mechanisms necessary for slowwave regeneration (12,37). Thus, propagation of slow waves, a critical feature of normal gastric motility, requires intact IC-MY networks throughout the phasic regions of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…The gastric interstitial cells of Cajal (ICC) act as pacemaker cells and possess unique ionic conductances that trigger slow wave activity, whereas smooth muscle cells lack the basic mechanisms required to generate ECA. Instead, cells of the latter type respond to the depolarization and repolarization cycle imposed by the ICC network and regulate L-type Ca 2+ currents which are also responsible for the contractile behaviour of the stomach (Horowitz et al 1999). In both animals and humans, the antral region of the stomach has the capability of a pacemaker which generates and drives ECA slow waves along the gastric corpus in the direction of the pylorus (Horiguchi et al 2001).…”
Section: Introductionmentioning
confidence: 99%